MENUJU BUDAYA HUKUM (LEGAL CULTURE) PENEGAK HUKUM YANG PROGRESIF - Antoni, Antoni (Nurani, 2019)
Legal culture is one of the important aspects that must be considered by legal functionaries in carrying out law enforcement, a culture consisting of values ​​and attitudes that can affect the way law works. By paying attention to the weaknesses that exist in this aspect of legal culture, it is expected that in the future Law Enforcement can change the paradigm not only individually but also institutionally in order to progressive Law Enforcement. Law Enforcement, who love the people and are loved by their people, make the law for humans. So that law enforcement can achieve the targets as desired, namely towards a just and prosperous society.